The toll of voting in a pandemic: Municipal elections and the spread of COVID-19 in Bavaria - Jochen Güntner (Johannes Kepler University of Linz, Department of Economics, 2020)
Elections may take place in precarious environments that even pose health risks. I consider the case of Bavaria, where close to ten million people were asked to vote in the municipal elections on March 15 of 2020, to quantify the toll of elections in a pandemic. Despite declaring a state of emergency on the very next day, two weeks later, Bavaria had left behind any other German state in terms of COVID-19 infections and deaths per capita. Using district-level health, demographic, and economic data, I find that at least 3,700 or 15% of the cumulative increase in positive test results between March 15 and April 4 are explained by a dummy variable for Bavaria. Across Bavarian districts, a 1% increase in voter participation is associated with an additional 13.6 positive tests and 1.2 deaths per 100,000 inhabitants over the following three weeks.
Keywords: H11; H12; I12; I18; 330; COVID-19; municipal elections; pandemic; synthetic control method